Sulfur metabolism: a versatile platform for launching defence operations - Rausch, Thomas; Wachter, Andreas (Trends in plant science, 2005)
Sulfur-containing defence compounds (SDCs) are crucial for the survival of plants under biotic and abiotic stress. SDCs include elemental sulfur (S0), H2S, glutathione, phytochelatins, various secondary metabolites and sulfur-rich proteins. Their constitutive and/or stress-induced formation is intimately dependent on demand-driven sulfate uptake and assimilation. Here, we highlight the complex network of plant SDCs and report on recent breakthroughs in our understanding of sulfur assimilation and how its regulation impinges on SDC function. These new insights have led us to revisit the hypothesis of ‘sulfur-induced resistance’, which claimed a prominent role for ‘extra’ sulfur nutrition in the defence potential of plants.